The Classical and Early methods of myringoplasty and tympanoplasty-I. - Soewito Soewito (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
There is still a controversial vision about the appropriate time to carry out myringotomy or tympanoplasty-1 on chronic otitis media. Some experts agree that the most appropriate time is two or three months after dry tympanic cavity (Classical method). Other experts state that it is not necessary to wait too long, even though there is still mucoid discharge, surgery can be directly caned out (Early method).The myringoplasty and tyrnpanoplasty-I was carried out on 72 cases of active chronic otitis media, of which 43 cases using Classical method and the rest of 29 cases using Early method. The criteria of successful myringoplasty and tympanoplasty-1 surgery was a positive graft take and followed by improvement of hearing.The successful result of myringoplasty and tympanoplasty-I with Classical method was 93.02 % and with Early method was 89.65%. The statistical analysis showed that there is no significant difference in the succesful of the myringoplasty and tymphanoplasty-I surgery, between the Classical and Early method.Key Words: myringoplasty tympanoplasty-I chronic suppurative otitis media classical method early method.